Oxytocin increases willingness to socially share one's emotions. (3rd May 2012) - Lane, Anthony; Luminet, Olivier; Rimé, Bernard; Gross, James J.; de, Philippe; Mikolajczak, Moïra
<x xml:space="preserve">Abstract</x> Oxytocin (OT) is a neuropeptide that is attracting growing attention from researchers interested in human emotional and social behavior. There is indeed increasing evidence that OT has a calming effect and that it facilitates pair‐bonding and social interactions. Some of OT's effects are thought to be direct, but it has been suggested that OT also may have indirect effects, mediated by changes in behavior. One potentially relevant behavioral change is an increased propensity for "emotional sharing" as this behavior, like OT, is known to have both calming and bonding effects. In this study, 60 healthy young adult men were randomly assigned to receive either intranasal placebo (PL; n = 30) or oxytocin (OT; n = 30). Participants were then instructed to retrieve a painful memory. Subsequently, OT and placebo participants' willingness to disclose to another person event‐related facts (factual sharing) vs. event‐related emotions (emotional sharing) was evaluated. Whereas the two groups were equally willing to disclose event‐related facts, oxytocin was found to specifically increase the willingness to share event‐related emotions. This study provides the first evidence that OT increases people's willingness to share their emotions. Importantly, OT did not make people more talkative (word counts were comparable across the two groups) but instead increased the willingness to share the specific component that is responsible for the calming and bonding effects of social sharing: emotions. Findings suggest that OT may shape the form of social sharing so as to maximize its benefits. This might help explain the calming and bonding effects of OT.